2020
DOI: 10.1002/aenm.202070031
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Batteries: Stable Nano‐Encapsulation of Lithium Through Seed‐Free Selective Deposition for High‐Performance Li Battery Anodes (Adv. Energy Mater. 7/2020)

Abstract: In article number 1902956, Ming‐Sheng Wang and co‐workers demonstrate the concept of nanoencapsulation of Li metal via seed‐free Li deposition inside carbon nanospheres by in situ electron microscopy. Such spheres enable Li filling in a highly reversible and repeatable manner, achieving dendrite‐free battery anodes with high cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…12-0254) is derived from the slight oxidation of lithium. [33] Moreover, after fully delithiation, the diffraction ring of Li 2 S (422) is disappeared, but those of ZnS (440), (511), and Sn (301) are generated again in Figure 5n, indicating an extraordinary performance with a dynamic particle change, superior structural and mechanical stability, and the excellent electrochemical reversibility can be achieved. [34] To further investigate the interfacial interaction of ZnS/Sn heterojunction from the theoretical viewpoint, DFT calculations were adopted.…”
Section: Resultsmentioning
confidence: 99%
“…12-0254) is derived from the slight oxidation of lithium. [33] Moreover, after fully delithiation, the diffraction ring of Li 2 S (422) is disappeared, but those of ZnS (440), (511), and Sn (301) are generated again in Figure 5n, indicating an extraordinary performance with a dynamic particle change, superior structural and mechanical stability, and the excellent electrochemical reversibility can be achieved. [34] To further investigate the interfacial interaction of ZnS/Sn heterojunction from the theoretical viewpoint, DFT calculations were adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Wang's group also reported the nano‐encapsulating electrode materials based on nitrogen‐doped hollow porous carbon spheres (N‐HPCSs) to tackle the major hurdles for the practical application of LMAs. [ 34 ] The thin N‐rich dense layer on the inner surface of N‐HPCSs can induce the preferential nucleation of metallic Li inside the hollow sphere. A highly reversible and repeatable plating/stripping cycling can be also achieved due to the specific structural design and stable Li encapsulation.…”
Section: Self‐lithiophilic Carbon‐based Materials As Current Collecto...mentioning
confidence: 99%
“…Recent investigations have demonstrated that heteroatom doping can increase the lithiophilicity of carbon‐based materials. [ 33–36 ] Monodisperse N‐doped hollow carbon nanospheres (NHCNSs) with large cavity fabricated by Liu et al. can serve as the robust host to endow the proposed LMA with outstanding stability even at the areal capacity up to 10 mA h cm −2 .…”
Section: Self‐lithiophilic Carbon‐based Materials As Current Collecto...mentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] PHCSs are also an ideal model system for operando TEM experiments for studying specific details of electrochemical processes since they do not require additional TEM sample preparation, provide necessary electron-beam transparency, and their structure/chemical composition can be easily adapted for further optimization. [21] Several possible sodium storage mechanisms, such as insertion, adsorption, the combination of adsorption and insertion, and the multistage mechanism, have been proposed in the literature. [22][23][24][25][26] For instance, Dahn et al suggested that sodium follows the insertion-adsorption mechanism during storage in hard carbons.…”
Section: Introductionmentioning
confidence: 99%